The flags of the right in politics - Auccatoma-Tinco, Roly (2023)
The critical analysis of the flags of the right is covered from philosophy and politics. The right openly defends neoliberalism, whose emblem is constituted by private property conceptualized by Hegel as the prolongation of the self; the conception of inequality that always evokes Hobbes; and the freedom of the market that is proclaimed loudly. The globalized world is monopoly capitalist and neoliberal, since there are large corporations that regulate prices, although they will always promulgate Hayek's neoliberal formula that refers to little State intervention and market deregulation, which are stipulated as the ten principles or commandments of neoliberalism, raised by John Williamson, to advance towards the progress established by the North Americans.